Do remittances and social assistance have different impacts on expenditure patterns of recipient households? The Moldovan Case. (2nd September 2017) - Waidler, Jennifer; Hagen-Zanker, Jessica; Gassmann, Franziska; Siegel, Melissa
Abstract : Do remittances and social assistance transfers have different impacts on household's expenditure patterns? While two separate strands of literature have looked at how social assistance or remittances have been spent, few studies have compared them directly. Using data from a household survey conducted in Moldova in 2011, this paper assesses the impact both types of transfers have on household expenditure patterns. Contrary to the common assumption that money is fungible, we find that social assistance and remittances have different impacts on expenditure patterns (having controlled for potential endogeneity). In other words, where the income comes from can determine how it is spent. As such, different sources of income may have different poverty impacts. In our sample, the two types of transfers are received by different, but slightly overlapping population groups. The fact that the two transfers are spent in different ways means that, to some extent, social assistance and remittances are complements rather than substitutes.